2018
DOI: 10.1021/acs.jmedchem.8b00421
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Discovery of a Potent, Orally Bioavailable Inhibitor That Modulates the Phosphorylation and Catalytic Activity of ERK1/2

Abstract: Aberrant activation of the MAPK pathway drives cell proliferation in multiple cancers. Inhibitors of BRAF and MEK kinases are approved for the treatment of BRAF mutant melanoma, but resistance frequently emerges, often mediated by increased signaling through ERK1/2. Here, we describe the fragment-based generation of ERK1/2 inhibitors that block catalytic phosphorylation of downstream substrates such as RSK but also modulate phosphorylation of ERK1/2 by MEK without directly inhibiting MEK. X-ray crystallographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 29 publications
6
57
0
Order By: Relevance
“…It is well known that kinases may adopt multiple conformations depending on the ligand structures. ERK enzymes are not an exception since, for instance, it has been reported that the isoform ERK-2 may adopt multiple conformations depending on the nature of the ligands [65]. In both 4QTA and 4QTB, Tyr27/Tyr30 are present as ‘in’ conformations.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that kinases may adopt multiple conformations depending on the ligand structures. ERK enzymes are not an exception since, for instance, it has been reported that the isoform ERK-2 may adopt multiple conformations depending on the nature of the ligands [65]. In both 4QTA and 4QTB, Tyr27/Tyr30 are present as ‘in’ conformations.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, six series of chemical fragments are rapidly built from our developed cMAVIs in two steps. These high-quality fragments are demanded in the drug discovery, especially in the fragment-based approaches ( Alen et al., 2019 ; Heightman et al., 2018 ; Kirsch et al., 2019 ).
Figure 4 DOS Strategy Applied to Construct Heterocyclic Fragments from 1a and 1a-Alike cMAVIs Note: Unless stated, otherwise R, R 1 , and R 2 stand for H; DCE, 1,2-dichloroethane; NBS, N -bromosuccinimide.
…”
Section: Resultsmentioning
confidence: 99%
“…We performed computational docking analysis of A1541-A1543 compounds against the ERK1/2 protein. A recent study has shown that the ERK1/2 specific inhibitor EQW ( 5-chloranyl-~[12]-(oxan-4-yl)pyrimidin-2-amine, PDB# 6G91) binds pocket B of the kinase [17]. Interestingly, like EQW, Cedrelone was found to occupy pocket B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical use of these upstream inhibitors often results in drug resistance through amplification of the ERK1/2 gene [21, 22]. To overcome this, Heightman TD et al, recently used a fragment-based library to identify the ERK1/2 inhibitor EQW [17]. While the anti-cancer activity of EQW has not yet been determined, ERK1/2 inhibitor Cedrelone identified in this study binds to similar binding pocket in ERK1/2 as does EQW, resulting in inhibition of the ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%